2023
DOI: 10.1007/s40675-022-00243-4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Performance in Professional Athletes

Abstract: Purpose of Review Sleep is an essential human behavior that plays a key role in proper biopsychosocial development as well as short- and long-term biological, physical, psychological, and cognitive health. Sleep plays a key role in athletic performance, influencing an athlete’s ability to train, recover, and perform, as well as their overall wellness. Over the recent decade, the awareness of sleep’s import has penetrated just about every professional sport domain. The purpose of the review was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 83 publications
0
25
0
Order By: Relevance
“…For example, coaches should consider athletes' chronotypes when designing training and travel schedules. 22,57 Finally, sleep disorders and symptoms may be difficult to identify in nonspecific health evaluations and require focused screening. 6 This is especially pertinent, as athletes from both countries had poor sleep quality scores yet did not rate their sleep as poor on the subjective sleep item of PSQI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, coaches should consider athletes' chronotypes when designing training and travel schedules. 22,57 Finally, sleep disorders and symptoms may be difficult to identify in nonspecific health evaluations and require focused screening. 6 This is especially pertinent, as athletes from both countries had poor sleep quality scores yet did not rate their sleep as poor on the subjective sleep item of PSQI.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the associations found with chronotype and sleep-related factors in this study warrant consideration in strategies to improve sleep. For example, coaches should consider athletes’ chronotypes when designing training and travel schedules 22,57 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that poor sleep has negative impact on athletic performance (Charest and Grandner, 2020, Craven et al, 2022). Conversely, increased sleep duration and quality are associated with improved performance and competitive success (Watson, 2017; Cook and Charest, 2023).…”
Section: Good Sleep Is Critical For Optimal Athletic and Academic Per...mentioning
confidence: 99%
“…Thus, it has been observed that in volleyball, consecutive matches affect heart rate variability ( 29 ); while in basketball, consecutive matches affect kinematic demands (relative distance, high intensity running, peak speed, deceleration) ( 30 ), as well as physical condition and psychological state ( 31 ). In esports, studies on the influence of congestion resulting from consecutive matches are practically nonexistent, but it has been observed that weeks with a higher number of games lead to poorer sleep quality for players ( 32 ). The absence of research on game congestion in esports becomes even more relevant when considering that in esports, the psychological component is more predominant than the physical one, and alterations of the psychological state are associated with disruptive behaviors during games ( 33 , 34 ).…”
Section: Introductionmentioning
confidence: 99%